Multi-dimensional temperature sensitivity of protected tropical mountain rain forests - Finegan, Bryan; Delgado, Diego; Hernández Gordillo, Alba Lorena; Zamora Villalobos, Nelson; Núñez Florez, Rafael; Díaz Santos, Fabio; Vílchez Mendoza, Sergio (Frontiers in Forests and Global Change, 2024)
Introduction Tropical mountain rain forests (TMRF, natural forests at > 300 m asl) are globally important for biodiversity and ecosystem services and are believed to be highly vulnerable to climate change. But there are no specific approaches for rigorous assessment of their vulnerability at the landscape and local scales necessary for management for adaptation. We address the challenge of evaluating the ecological sensitivity to temperature of TMRF, applying a multidimensional approach in protected areas over a 440–2,950 m asl altitudinal gradient in Costa Rica, synthesizing results of a long-term research programme (2012-present). We evaluate the sensitivity to the current spatial temperature gradient of eleven ecosystem properties in three categories: forest composition and diversity, thermal characteristics of forest stands and forest structure and dynamics. Methods Data are from 29 to 32 plots of 50 m x 50 m (0.25 ha) distributed over the gradient, in which all trees, palms and tree ferns ≥ 10 dbh are identified to species and measured for recruitment, growth and mortality. An experimental study of leaf litter decomposition rates was carried out in twelve plots. Current and future (SSP 585, 2070) values of mean annual temperatures MAT were obtained from online climate surfaces. Thermal characteristics of forest stands were determined using MATs of species occurrences in GBIF and include a new index, the Community Thermal Capital Index (CTCI), calculated as CTI-MAT. Results We classified degrees of sensitivity to temperature as very weak, weak, moderate or substantial. All eleven ecosystem properties are substantially sensitive, so changes in their values are expected under rising temperatures. Species density, the community temperature index CTI, tree recruitment and mortality rates and leaf litter decomposition rates are positively related to temperature, while the community weighted mean thermal niche breadth, the CTCI, net basal area increments, stand basal area and carbon in aboveground biomass are negatively related. Results point to zones of vulnerability in the protected areas. Discussion In montane forests, positive values of the CTCI–climate credit– robust basal area growth and very low mortality and leaf litter decomposition rates suggest healthy ecosystems and no risk of mountaintop extinction. Lowland forests may be vulnerable to degradation and biotic attrition, showing current basal area loss, high mortality and climate debts. National and local actors are participating in a process of adoption of the sensitivity analysis and recommendations regarding zones of vulnerability.